Arheologija afekta - Littau, Karin (Primerjalna književnost, 2011)
Literary history is filled with stories of reading as a deeply affective experience. Why does our own age deem such reactions trivial? And why is affective reading almost exclusively now associated with women readers?
Keywords: zgodovina branja; bralne navade; woman; ženske; literarno izkustvo; afektivno branje